Learners’ Perceptions and Experiences in Using AI to Learn English: An Exploratory Study in an EFL Context - Maulida, Nimas Ayu Nawal; Prasetyarini, Aryati (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to explore the role of artificial intelligence (AI) in improving English language learning among high school students in a bilingual school in Surakarta, Indonesia. Although AI is increasingly being integrated into the curriculum, more is needed to know about students’ experiences using AI for language learning, especially regarding technical challenges and their limited understanding of this technology. Methodology: This qualitative study used document analysis, observation, and semi-structured interviews with students and teachers based on Creswell’s (2014) qualitative approach. Participants were selected by purposive sampling, consisting of students in grades X, XI, and XII who use AI tools such as Duolingo and Google Translate. Results: Findings showed that although students found personalized feedback from AI tools helpful, challenges such as internet connectivity issues and limited linguistic feedback reduced their effectiveness. Some proposed solutions include developing more adaptive AI tools, improving technological infrastructure, and providing AI literacy training to enable students to utilize these technologies more optimally. Applications/Originality/Value: In addition, integrating AI with more diverse traditional teaching approaches can increase student motivation and reduce over-reliance on technology. This research provides new insights into AI’s challenges and potential uses in language education, emphasizing the need to balance technology and conventional learning methods. The development of more interactive and inclusive AI tools and AI literacy education can support the maximum utilization of this technology in bilingual education environments.